The Use of Digital Comics in the EFL Contexts: A Systematic Review of Quantitative Studies - Komang Icha Sri Handayani; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
The integration of technology in education has improved the efficacy of pedagogical activities, making it easier for both teachers and students. Digital comics with their captivating features could attract learners and improve outcomes in English as a Foreign Language (EFL). This systematic literature review with content analysis synthesized nine articles from educational journals (2020-2025) to investigate research trends and the effectiveness of digital comics on English language skills. The current study found that the quantitative approach with a quasi-experimental design using pre-test and post-test instruments dominated the trend, with undergraduate students as the most studied group. The application used varies between custom web-based tools and existing platforms like Webtoon. Targeted skills range from primary-level literacy to Higher-Order Thinking Skills (HOTS) for standardized tests such as the TOEFL. Finally, the findings suggest that digital comics are proven effective as media for enhancing English skills across various educational levels.